Teaching Factory Implementation to Grow the Entrepreneurship Character of Vocational School Students - Marsudi Endang; Tri Kuat (Journal of Vocational Education Studies, 2023)
The purposes of this study are 1. To analyze the application of teaching factory (TEFA) in the mechanical engineering expertise program at SMK M Sukoharjo, 2. To analyze the reinforcing and inhibiting factors for the application of TEFA in the mechanical engineering expertise program at SMK M Sukoharjo, 3. To analyze the application of TEFA in growing entrepreneurial character of students in the mechanical engineering expertise program at SMK M Sukoharjo. The research method is qualitative descriptive research. The data collection technique used three techniques, namely structured interviews, field observations and data documentation. The informants were school principals, deputy heads of school curriculum, heads of mechanical engineering study programs, productive teachers, and students. Data validity using source triangulation by comparing different sources. Data analysis techniques using interactive data analysis which includes data collection, data reduction, data presentation, data verification, and drawing conclusions. The results of the study found were 1. Application of Teaching Factory (TEFA) in the mechanical engineering expertise program at SMK M Sukoharjo seen from the application of management functions which include planning that has been made well, the organization has been made into an organizational structure that involves all elements in the school, the implementation is in accordance with implementation standards in the industry, supervision is carried out in stages. 2. The reinforcing factors for the success of TEFA are; a. Adequate infrastructure both in terms of quantity and quality b. Qualified human resources, c. Quality products d. How to work in accordance with industry standards e. Extensive marketing mix. The inhibiting factor is a. Student motivation is still low, b. Low student morale, 3. The application of TEFA can foster the entrepreneurial character of students by involving students in TEFA activities.